Study of sporoderm pattern under SEM in the genus Bryum - Bansal, Pooja; Nath, Virendra (Phytotaxa, 2013)
A critical study of sporoderm pattern under SEM in nine taxa of genus Bryum, growing in various bryogeographical regions of India, has been carried out. Of these nine taxa, microdetails of sporoderm pattern of six taxa: B. billardieri, B. caespiticium, B. capillare, B. dichotomum, B. pseudotriquetrum var. subrotundum and B. uliginosum are provided for the first time.